(3GdebGeI GdfNjdjI hTQMgG GdeSei (B: (3GdEcdjd aj aVd GdfNjds - (3Ydj Hf YHO Gddg Hf eMeO Hf eMeO GdLPGej GdeGdbj GdfHGgj, GHf GdMSf,J (B792 (3g` s
(3ChdgG (B:s
(3bdJ CNGWH ef CLQi ef GdSQGJ PcQ GdYQGb eGgGL GdfaS GdTYGY dh CYL GdCThGb s
(3BNQgG (B:s
(3Gddge jGef dG JNGdWg GdXfhf habfG Edi hYi eG JVefg ef GdfUGFM bOJe GdJbjjO HMeO Gddg s
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B306s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(328 (3b(B) s
Keywords: (3GdCOHs